2017
DOI: 10.1038/boneres.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate cements for bone engineering and their biological properties

Abstract: Calcium phosphate cements (CPCs) are frequently used to repair bone defects. Since their discovery in the 1980s, extensive research has been conducted to improve their properties, and emerging evidence supports their increased application in bone tissue engineering. Much effort has been made to enhance the biological performance of CPCs, including their biocompatibility, osteoconductivity, osteoinductivity, biodegradability, bioactivity, and interactions with cells. This review article focuses on the major rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
203
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(229 citation statements)
references
References 167 publications
6
203
1
5
Order By: Relevance
“…Previous studies demonstrated that the exural strength of the CPCchitosan composite scaffold was 19.8 MPa, which was more than 2 folds of the 8 MPa for the CPC control without chitosan. 30,41 The strength of CPC-chitosan composite scaffold exceeded the exural strength of sintered porous hydroxyapatite (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and the tensile strength of cancellous bone (3.5 MPa), thus rendering the CPC-chitosan composite scaffold promising for a wide range of orthopedic, dental and craniofacial applications. 30,41 Furthermore, the CPC-chitosan scaffold has potential to serve as a delivery vehicle for drugs and growth factors to promote bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that the exural strength of the CPCchitosan composite scaffold was 19.8 MPa, which was more than 2 folds of the 8 MPa for the CPC control without chitosan. 30,41 The strength of CPC-chitosan composite scaffold exceeded the exural strength of sintered porous hydroxyapatite (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and the tensile strength of cancellous bone (3.5 MPa), thus rendering the CPC-chitosan composite scaffold promising for a wide range of orthopedic, dental and craniofacial applications. 30,41 Furthermore, the CPC-chitosan scaffold has potential to serve as a delivery vehicle for drugs and growth factors to promote bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In one formulation, the CPC powder consists of a mixture of tetracalcium phosphate (TTCP) and dicalcium phosphate anhydrous (DCPA). 5 A CPC paste can be formed by mixing the CPC powder with a CPC liquid, leading to apatite precipitation as the end product. 5 Combining cells with scaffolds is a potent strategy in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they are similar to the hydroxyapatite (HA) mineral phase of natural bone and teeth, CPCs are widely used as repair materials for fractures or bone defects. CPC can be easily molded or injected into the irregular cavity of bone tissue to restore bone structure and function and stimulate new bone formation (Xu et al, ). Because HA is the most stable (least soluble) compound over a very wide pH range (4.4 and above), most neutral pH CPC formulations form HA or other closely related apatitic phases, for example, Ca‐deficient HA, carbonated HA, other nonstoichiometric HA, and so on, as products (Chow, ; Dorozhkin, ); these products have dense structures and cannot provide rapid bone regeneration due to their slow degradation.…”
Section: Introductionmentioning
confidence: 99%
“…A synthetic multi-phased calcium phosphate, such as HA/a/b-TCP/CPP, could combine the advantages of the components for bone repair. [28][29][30][31][32] Especially for CPP, Palmer et al, reported that CPP could have the potential effect of osteoinduction under a certain content. 20 Introducing a small amount of CPP into a multi-phased bioceramic graft could enhance its osteogenic properties.…”
Section: Introductionmentioning
confidence: 99%